Prevalence of depression among patients with type 2 diabetes mellitus and its predictions : a cross sectional study in primary care setting, Malaysia. - Md Aris, Mohd Aznan; Mohamed, Abdul Hadi; Tin, Myo Han; Johari, Ahmad Hafizuddin; Izamuddin, Muhammad Syafeeq; Muhammad Yusof, Muhammmad Khairulahnaf (2018)
Objectives: The prevalence of depression among patients with diabetes mellitus has been reported to be higher than normal population. This study assessed the prevalence of depression among patients with type 2 diabetes mellitus in east coast Malaysia and its associated factors. Methods: A cross sectional study was done on 103 patients with type 2 diabetes mellitus attended primary care clinic in Kuantan, Malaysia from July to August 2015. A selfadministered questionnaire using the validated Depression and Anxiety Stress Scales 21 (DASS 21) Malay version was used to assess the level of depression among patients with type 2 diabetes mellitus. The questionnaire also comprised of sociodemographic and clinical characteristics of patient in order to assess for association. Association were tested using chi square test and logistic regression. Results: Of 103 patients with type 2 diabetes mellitus, the prevalence of depression was 12.6%. Female gender and recent significant life event were significantly associated with depression (p<0.05). Conclusion: Depression is a common condition associated with diabetes mellitus and it has significant relationship with gender and recent significant life event. Physicians managing patients with diabetes mellitus should therefore take the initiative to screen this condition at any given opportunity especially among female patients and patients with recent significant life event.